Dibenzo phenazine-containing carbazole compound, preparation method and application of dibenzo phenazine-containing carbazole compound - HAN LIANG; GAO JIANRONG; XU MENG; LIU YANG (2017)
The invention provides a dibenzo henazine-containing carbazole compound, and belongs to the technical field of dye sensitizers. The dibenzo henazine-containing carbazole compound has a structure shown in formula 1: formula 1 is shown in the description, where R comprises a compound shown in the description, a compound shown in the description or a compound shown in the description. A dye-sensitized solar cell assembled by the compound as a dye sensitizer has relatively high photoelectric conversion efficiency which is 2.78 to 8.15 percent, and a new substance available for dye sensitizer screening is added. 本发明提供了种含二苯并吩嗪的咔唑类化合物，属于染料敏化剂技术领域，具有式1所示结构：式I中，R包括或该化合物作为染料敏化剂组装成的染料敏化太阳能电池具有较好的光电转换效率，光电转换效率为2.78～8.15％，为染料敏化剂的筛选增添了新的可应用物质。